Contract Cheating in Canada: National Policy Analysis Project Update and Results for 2021 - Eaton, Sarah Elaine; Stoesz, Brenda M; Miron, Jennie; McKenzie, Amanda; Devereaux, Lisa; Steeves, Marcia; Godfrey Anderson, Jennifer; LeBlanc-Haley, Joanne (Canadian Perspectives on Academic Integrity, 2021)
Join us for an in-depth look at how contract cheating is addressed in Canadian higher education policies. In this session we share results synthesized from 80 publicly-funded universities and colleges across Canada, where English is the primary language of instruction. Our results show why Canada is lagging behind in terms of addressing contract cheating pro-actively through policy and procedures. We offer concrete recommendations for improving the ways that Canadian schools can address contract cheating and other breaches of academic integrity through policy and procedures. In this study, regional teams assembled to collect and analyze academic integrity policies from 80 publicly-funded universities and colleges across Canada where English is the primary language of instruction (Western Canadian universities, n = 24; Ontario universities, n = 21; Atlantic Canadian universities, n = 13; Ontario colleges, n = 22). Although the entire study is not yet complete, we now have full or preliminary results to share from 9 Canadian provinces (BC, AB, SK, MB, ON, NB, NS, PE, and NL). In this session we offer the most comprehensive synthesis of the project to date. In our presentation we provide an overview of the project as a whole, show how we have conducted the study (i.e., method), and present our findings at both a regional and national level. Based on our findings, we offer evidence-based recommendations for policy reform for academic integrity in Canadian higher education, concluding with a call to action for policy makers and administrators to take a stronger stance against contract cheating. For more information on this project visit https://osf.io/n9kwt/.